Research and practice of network security threat intelligence management system for power enterprise - Weixiong CHEN; Xiaochen YANG; Zengjun CHUN; Ruolan LI; Hua ZHANG (Dianxin kexue)
Network security is an important part of the national security, and network security threat intelligence work has become an important part of the network security protection.Aiming at the problems of power enterprise carrying out network security threat intelligence, such as many sources, many types, wide range, many vulnerability risks, many subordinate departments and personnel, the network security threat intelligence work plan of power enterprise was put forward.The scheme includes five aspects: information source, information research and judgment, information disposal, information platform and information performance.The evaluation method of network security vulnerabilities, information emergency disposal process and information performance evaluation method were puts forward.The preliminary application results show that the proposed scheme has important reference value for power enterprise to improve the emergency response ability of network security information and the level of network security protection ability.